Supporting SDGs Through Efficient Technology by Implementing PDCA and Renewable Energy at PT. Dharma Electrindo - Agustin Sukarsono; Putut Ade Irawan; Johan Alfian Pradana (Universitas Airlangga, 2024)
The SDGs, launched by the UN in 2015, replaced the MDGs with 17 goals, focused on eliminating poverty, environmental protection, and global prosperity. PT. Dharma Electrindo Manufacturing adopts environmentally friendly technology to save energy and reduce emissions, supporting SDGs. Without the SDGs, there is a need for innovation in manufacturing technology to support SDGs 8, 12, and 13. This study will improve the sustainability of the industry. This research analyzes the effectiveness of energy and environmental improvements at PT. DEM in supporting SDGs. This research design uses a descriptive qualitative approach with a Plan-Do-Check Action cycle to improve energy efficiency and reduce emissions at PT. Dharma Electrindo MFG, with data collected through questionnaires, checklists, and monitoring. Studies show the SDGs are effective for some goals, but cost and weather dependency hinder the efficiency of innovative technologies. The application of efficient technology and PDCA methodology at PT. DEM improves energy and environmental management, reduces emissions by 12% per year, and increases operational efficiency. The implementation of LED lights, automatic watering systems, and renewable energy technology supports SDGs by reducing electricity consumption by 21,790.12 kWh. Theory and practice show PDCA technology supports energy efficiency and the SDGs.